Modeling of urease thermal inactivation processes in soybean at high-temperature micronization - Zverev, Sergey; Sesikashvili, Otari (Potravinarstvo Slovak Journal of Food Sciences, 2018)
The use of soybean, in particular in forage production without preliminary heat treatment is not appropriate, and sometimes dangerous, because of the presence of antinutrients. As a marker in assessing safety of cakes and meals, there is often used urease in forage production. This paper describes the results of thermal inactivation of urease in soybean during the process of high-temperature micronization (heating of grain in the flux of infrared radiation). There have been obtained the empirical dependencies of the degree of its inactivation on time of heat treatment and energy exposure (the product of irradiation by the time of treatment). The similar dependences of urease activity on grain temperature are invariant to infrared heating (irradiation and time) regimes, but their nature is affected by the initial moisture content. The paper proposes the models of inactivation of antinutrients based on of the first-order equations of chemical kinetics with the reaction rate constant in various forms (Arrhenius and Hinshelwood, the transition state theory). The models have been tested on literature data on the inactivation of a trypsin inhibitor at a constant temperature. The models are further refined taking into account the variable (increasing) temperature and are reduced to the simplest form: Y= k [Exp (-εR/T) - T0 еxp (-εR/T0)], where T, T0- are the current and initial temperatures of grain, k, εR - theempirical coefficients. The identification of the model coefficients was carried out based on the results of inactivation of urease during heating in the flux of infrared radiation. It has been established that the results of thermal inactivation of soybean do not depend on the IR processing regimes and are determined only by the initial moisture content of grain, and by the end heating temperature. The efficiency of inactivation is higher the higher is the used irradiation. There is a compensating effect - with the growth in one coefficient, another is also increased. The considered models can be used for the thermal degradation processes and other thermolabile substances.